2017
DOI: 10.1021/acsphotonics.7b00538
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of the Rabi Splitting under Nonlocal Corrections in Plexcitonics

Abstract: We explore theoretically how nonlocal corrections in the description of the metal affect the strong coupling between excitons and plasmons in typical examples where nonlocal effects are anticipated to be strong, namely small metallic nanoparticles, thin metallic nanoshells or dimers with narrow separations, either coated with or encapsulating an excitonic layer. Through detailed simulations based on the generalised nonlocal optical response theory, which simultaneously accounts both for modal shifts due to scr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 110 publications
0
39
0
Order By: Relevance
“…Since this is practically impossible, we focus here on a NP with similar linewidth and resonance position of its lower-energy mode before coupling -in plasmonics, this is of course ian electric dipolar mode. To tune the plasmon mode at 1.76 eV, we consider silica-gold nanoshells (ε silica = 2.13) instead of homogeneous gold spheres, and introduce plasmon hybridisation as a mode shifting mechanism [48,49]. For a silica core of radius 19.5 nm, total nanoshell radius (R 1 in the previous context) 25 nm, and D = 20 nm, the extinction spectrum of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since this is practically impossible, we focus here on a NP with similar linewidth and resonance position of its lower-energy mode before coupling -in plasmonics, this is of course ian electric dipolar mode. To tune the plasmon mode at 1.76 eV, we consider silica-gold nanoshells (ε silica = 2.13) instead of homogeneous gold spheres, and introduce plasmon hybridisation as a mode shifting mechanism [48,49]. For a silica core of radius 19.5 nm, total nanoshell radius (R 1 in the previous context) 25 nm, and D = 20 nm, the extinction spectrum of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, although similar systems have already been investigated by some of the authors of this article [70], this result has not been observed before. On the contrary, Tserkezis et al [56,71] have demonstrated robustness of strong coupling against nonlocal corrections, when collective emitters are considered. As we will see later, however, this behavior is hindered in the vicinity of noble metal systems, since photon emission spectra are strongly affected by d-band transitions.…”
Section: Spheresmentioning
confidence: 98%
“…The closer they are to a nanoplasmonic system, the more efficiently their fields can probe nonlocal and quantum effects in the metal response [1][2][3][4]. Recent studies have highlighted the impact of nonlocality on single-emitter weak coupling [53][54][55], as well as in plasmon-exciton systems in the strong coupling regime [56]. Quantum effects have also been investigated in metals, in plasmon-exciton systems [57], and in molecules, beyond the point-dipole approximation [21].…”
Section: Introductionmentioning
confidence: 99%
“…Thus an extended criterion is demanded. When the detuning is smaller than ω ex , the splitting of plexcitonic states can be approximately expressed in the form of ℏΩ 0 through the classic description of strong coupling E+E=Ω02+δifalse(WnormalexWnormalplfalse)2. When ℏΩ 0 > ℏ W ′ ex + ℏ W ′ pl , the system with δ not equating to 0 achieves the strong coupling regime.…”
mentioning
confidence: 99%